Job Empowerment and Participative Decision Making Concerns at Abu Dhabi Group: A Qualitative Case Study - Sarwar, Huma (Archives of Business Research, 2017)
Employee empowerment and participative decision making practices have been used from long time ago that make employees to use the inborn capabilities to attain their personal unique excellence at workplace, by doing this organizational effectiveness and individual efficiency could be achieved for greater performance. Empowering the employees is taken as enhancing decision making abilities among the lower level employees and give confidence to do a difficult tasks that leads to improve individual’s experience at worksite. Despite the importance of these significant human resource functions, Telenor faced terrible issues with lower level management because of their non-directed and non-employee oriented strategies. This report is described these issues with their key actions that may benefit for the organization after implementation.